2017
DOI: 10.1186/s13287-017-0640-0
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stromal cells ameliorate oxidative stress-induced islet endothelium apoptosis and functional impairment via Wnt4-β-catenin signaling

Abstract: BackgroundIslet dysfunction and destruction are the common cause for both type 1 and type 2 diabetes mellitus (T2DM). The islets of Langerhans are highly vascularized miniorgans, and preserving the structural integrity and full function of the microvascular endothelium is vital for protecting the islets from the infiltration of immune cells and secondary inflammatory attack. Mesenchymal stromal cell (MSC)-based therapies have been proven to promote angiogenesis of the islets; however, the underlying mechanism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 41 publications
1
41
0
Order By: Relevance
“…Moreover, Leroux et al (48) reported that MScs, via the Wnt4 pathway, improved skeletal muscle fiber regeneration following ischemic injury. Other studies have also demonstrated activation of the Wnt pathway by MScs (55)(56)(57). The present study found that, in the presence of hdPSc-cM, the levels of Wnt/β-catenin pathway-related proteins, including p-GSK-3β and β-catenin, were upregulated.…”
Section: Discussionsupporting
confidence: 72%
“…Moreover, Leroux et al (48) reported that MScs, via the Wnt4 pathway, improved skeletal muscle fiber regeneration following ischemic injury. Other studies have also demonstrated activation of the Wnt pathway by MScs (55)(56)(57). The present study found that, in the presence of hdPSc-cM, the levels of Wnt/β-catenin pathway-related proteins, including p-GSK-3β and β-catenin, were upregulated.…”
Section: Discussionsupporting
confidence: 72%
“…Wnt4 is a Wnt family protein that exhibits strong osteoinductive effect via noncanonical Wnt-signaling pathways (43,44). However, controversial data arguing against its activation of b-catenin also exist (45,46). In this study, we discovered that Wnt4 induced bone formation via both canonical Wnt-b-catenin and noncanonical Wnt-p38-JNK MAPK pathways in both MC3T3-E1 preosteoblasts and human MSCs.…”
Section: Osteopenia and Osteoporosis Caused By Chronic Inflammation-imentioning
confidence: 77%
“…A study in diabetic mice has shown that the injection of MSCs can restore vasculogenesis and blood flow in an ischemic hind limb 15 . Co-culture of islet endothelial cell with MSCs can prevent oxidative stress-induced apoptosis, eNOS inhibition and VCAM elevation 16 . A recent study found that local transplantation of MSCs improved cutaneous wound healing via promoting endothelial cells angiogeniesis, during which VEGF-paracrine secreted from MSCs plays a central role 17 .…”
Section: Introductionmentioning
confidence: 99%